Exploring the Relationship Between Dental Caries and Obesity in Makkah Children - Abdullah Marghalani; Ibrahim Alnefaie; Abdullah Hazzazi; Raed Alghamdi; Abdelaziz Khatry; Ahmed Balkhour; Salem Dehom (Journal of Umm Al-Qura University for Medical Science, 2023)
Background: Obesity and dental caries are global severe public health concerns. In Saudi Arabia, both diseases are increasing among children. This study aimed to evaluate the relationship between dental caries and obesity in children living in Makkah City. Methods: The study design was cross-sectional. The sample was obtained from a dental teaching hospital at Umm Al-Qura University (UQU) and an elementary school in Makkah. Dental caries was measured using the Decayed, Missing, or Filled Teeth (DMFT/dmft) index. Obesity was measured using age and gender-specific Body Mass Index (BMI). Several covariates were collected, including diet, lifestyle, demographic, and socioeconomic status, including diet, lifestyle, demographic, and socio-economic status, were collected. Results: The total sample size included 184 children. The mean dental caries measured by DMFT/dmft was 5.37 with a standard deviation of (3.8). About 25 (13.7%) of the included children were underweight; 112 participants (61.2%) had a normal weight; 18 participants (9.8%) were overweight, and 28 participants (15.3%) were obese. In the crude and adjusted analysis, underweight children had higher dental caries than average weight, and overweight/obese children had less dental caries than normal-weight children. Moreover, the socio-economic status of the parents showed a positive relationship with dental caries experience. Conclusions: Dental caries experience differed by BMI status. Overweight children had lower dental caries experience and underweight children had higher dental caries experience.